Bráðaofnæmi í tveimur landbúnaðarhéruðum á Íslandi : I. Tíðni bráðaofnæmis og helstu ofnæmisvaldar - Davíð Gíslason; Gravesen, Suzanne; Tryggvi Ásmundsson; Vigfús Magnússon (Læknafélag Íslands, Læknafélag Reykjavikur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) The aim of this study was to find prevalence of type I allergy and allergens which cause symptoms in two farming communities in Iceland. One community, V. Skaftafellssýsla, is located at the southern coast of Iceland, the country's heaviest rainfall area (2,000-4,000 mm/year). In spite of this, regular haymaking with outdoor drying of the hay is the most common method. After a wet summer one would expect to find moldy hay, generating a lot of dust. The other community, Strandasýsla, is located in the northwestern part of the country, where rainfall is low (1000-2000 mm/year) but the summer is very short. Therefore the farmer cannot risk a wet summer and makes silage from most of his harvest. The regular haymaking by outdoor drying is usually done under optimal circumstances, but the amount is small. An average farmer in this community therefore has the least haydust exposure in Iceland. We selected from the Icelandic National Registry all heads of household 50 year old and younger in these communities. All family members age 6-50 were examined. These age limits were used because allergic symptoms and skin tests tend to fade after the age of 50, and it is difficult to draw blood from young children. The British Medical Research Council questionnaire of respiratory symptoms was used with questions added regarding symptoms, possibly caused by type I allergy. If there were positive answers to any of these possibly allergic symptoms, a prick test was performed. The allergens used were the 12 standard allergens used in Iceland and 12 allergens found in the Icelandic hay. Skin test was positive if the reaction was 2 mm larger than negative control. We studied 319 individuals, 183 males and 136 females. Prick test was performed on 103. Of these 57 or 55% had one or more positive skin test. In V. Skaftafellssýsla 42 (27,6% of those studied) underwent prick test but 61 (36,5% of the study group) in Strandasýsla. ...